Angling for endangered fish: conservation problem or conservation action?. Issue 1 (15th February 2014) - Cooke, Steven J; Hogan, Zeb S; Butcher, Paul A; Stokesbury, Michael J W; Raghavan, Rajeev; Gallagher, Austin J; Hammerschlag, Neil; Danylchuk, Andy J
Abstract: Recreational angling has been implicated in population declines of some marine and freshwater fish, but this activity is rarely considered as a threat or even halted when endangered species are targeted. Indeed, in some cases, anglers are drawn to fish for rare or endangered species. Conservation‐oriented behaviours such as catch‐and‐release are often practiced voluntarily due to the ethics of anglers, yet even in these cases, some fishing mortality occurs. Nonetheless, there are many indirect conservation benefits associated with recreational angling. Here, we present a series of case‐studies and consider whether catch‐and‐release angling for endangered fish is a conservation problem or a conservation action. If recreational angling activities contribute to population‐level consequences that are contrary to recovery strategies, then angling for endangered species would seem to be a poor option. However, as revealed by several case‐studies, there is much evidence that anglers are vocal and effective proponents of fish and habitat conservation, and for endangered species, they are often the only voice when other stakeholders are not engaged. Anglers may contribute directly to conservation actions via user fees (e.g. licences), philanthropic donations or by volunteering in research, education and restoration activities. However, it is important to quantify post‐release mortality as well as understand the full suite of factors influencing a given population or species to know the potential risks. A risk assessment approach outlined in the paper may be used by managers to determine when the benefits of angling for endangered species outweigh the risks.